Analysis of Innovation in Aqedah Akhlak Learning with the Contextual Teaching and Learning Method in Environment-Based Madrasah: Case Study at Madrasah Ibtidaiyah Negeri (MIN) 1 Yogyakarta - Musyrifah, Farida; Fathurrohman, Rizal; Darmawan, Ferry; Yanti, Yanti (DAS Institute, 2024)
Contextual Teaching and Learning (CTL) is an innovative learning model in the Teaching and Learning Activities (KBM). This study aims to identify and analyze innovations in the teaching of the subject of Akidah Akhlak using the Contextual Teaching and Learning method in an environmentally-based Madrasah. In an era of education that increasingly demands relevance and applicability, the Contextual Teaching and Learning model is still considered an effective method for enhancing understanding and internalizing the values of akidah akhlak in everyday life. The focus of this research is Madrasah Ibtidaiyah Negeri 1 (MIN 1) Yogyakarta, which is one of the environmentally-based madrasahs with programs related to environmental preservation. This environmentally-based program requires a lot of learning outside the classroom, which can be integrated into the teaching of Akidah Akhlak using the CTL method. This study employs a qualitative method with a case study approach. The findings indicate that the implementation of innovative teaching of Akidah Akhlak with the CTL method in grade III at MIN 1 Yogyakarta has several notes: 1) the learning process runs well and is attended by all students; 2) the implementation of the CTL model is constrained by limited time; 3) the results show that the application of the CTL model in teaching Akidah Akhlak not only improves students' understanding of the material but also helps them apply religious teachings in their daily behaviour.